Factors Affecting The Performance Of Medan Mayor's Office Employees, Financial Division - Maharani, Anggun Debana; Nasution, Juliana (Widya Balina, 2023)
The purpose of this study was to find out how work discipline, leadership and appreciation for the achievements of employees of the Regional Finance and Assets Section. In this study, the author employed a quantitative descriptive methodology, which means that they used numbers to describe the study's condition. Techniques for gathering data include observation, interviews, exchanging surveys with staff, and studying the literature. 25 respondents in the Office and Finance Section of the Mayor of Medan Properti region were given questionnaires by the author. A Likert scale is used to measure the variables. he goal is to quantify the independent variable's influence on the dependent variable's dependability, which is 90% ( = 0.05). Taking the test findings collectively, it can be shown that the Medan Mayor's Office of Finance and Regional Assets' employee performance is positively and significantly impacted by work discipline, supervision, and reward.